A new Indian species of Rhinophis Hemprich, 1820 closely related to R. sanguineus Beddome, 1863 (Serpentes: Uropeltidae) - Sampaio, Filipa L.; Narayanan, Surya; Cyriac, Vivek Philip; Venu, Govindappa; Gower, David J. (Zootaxa, 2020)
A new species of the uropeltid (shieldtail snake) genus Rhinophis is described based on a type series of seven specimens from the Wayanad region of the Western Ghats of peninsular India. The holotype was collected before 1880 but had been misidentified as the phenotypically similar and parapatric (possibly partly sympatric) R. sanguineus. Rhinophis karinthandani sp. nov. is diagnosed by a combination of 15 dorsal scale rows at midbody, 4–8 pairs of subcaudal scales, colour pattern (uniformly dark above, whitish below with extensive dark mottling), and by its distinct mitochondrial DNA sequences (e.g. >7.6% uncorrected p-distance for nd4). Phylogenetic analysis of mitochondrial DNA sequence data indicates that the new species is most closely related to R. sanguineus among currently recognised species, with this pair most closely related to the partly sympatric R. melanoleucus. The new species description brings the number of currently recognised species in the genus to 24, six of which are endemic to India and 18 endemic to Sri Lanka. A new key to the identification of Indian species of Rhinophis is provided.